The Continuance Intention of User’s Engagement in Multiplayer Video Games based on Uses and Gratifications Theory - Ira Puspitasari; Elzha Odie Syahputra; Indra Kharisma Raharjana; Ferry Jie (Universitas Airlangga, 2018)
One of the key success factors in video game industry, including multiplayer video game (MVG), is the user’s continuance intention. The MVG industry runs in a highly competitive market. Users can shift to another game as soon as they discover a slightly inconvenient issue. Thus, maintaining the user’s enthusiasm in playing MVG for a long time is challenging for most games. The solution to prolong the users’ engagement can be initiated by identifying all factors that facilitate the continuance use of playing MVG. This study applied uses and gratifications theory to examine seven variables (enjoyment, fantasy, escapism, social interaction, social presence, achievement, and self-presentation) and the moderating effects of age and gender on the MVG continuance intention. The data analysis and the model development were tested based on Partial Least Square method using the responses of 453 MVG users. The results revealed that enjoyment, fantasy, social interaction, achievement, and self-presentation significantly affected the continuance intention of playing MVG, with enjoyment being the strongest variable. The result also demonstrated the moderating effect of age and gender on the relation between independent variables and continuance intention. The results and findings offered additional insights into the system development to enhance the information system application.